Desempenho agronômico, qualidade fisiológica e armazenamento de sementes de milho submetidas ao tratamento químico - Silva, Karen Marcelle de Jesus (2018)
Seed treatment is important to ensure suitable stands in maize. However, it is necessary to evaluate the influence of the products used on the physiological quality of the seeds, as well as their influence on the productive performance of the crop. In many companies it is considered important to store the seeds already treated with insecticides, thus maximizing the efficiency in the industrial process. Like this, the objective in the first work was to verify the effect of insecticide and fungicide treatment on the physiological quality of seeds of three maize hybrids, classified in two sizes, in different storage periods. In the second work aimed to evaluate the effect of the chemical treatment of maize hybrids seeds, classified in two sizes, submitted to different storage conditions, on the performance of the field crop. For both experiments, hybrids seeds 2B647PW, BM915 PRO and SHS4070, flat shape and classified in two sizes (CH20/64 and CH24/64), treated with Carbendazim + Tiram (Derosal Plus®), Deltamethrin (Actellic®), Pirimiphos methyl (K-obiol®) and water [standard treatment] were used. In addition to the standard treatment adopted by the company, treatments with clothianidin (Poncho®); thiamethoxam (Cruizer®) and fipronil (Shelter®) were added to the blend. In the first work the seeds were conditioned in paper bags multi-foliated in non-air conditioned environment. The physiological quality of the seeds was evaluated in the initial phase of the experiment and every 90 days for a period of 270 days, through germination tests, seedling emergence under controlled conditions, cold test and accelerated aging. The sanitary quality was also evaluated by Blotter test. In the second work, the seeds were submitted to three storage conditions to be sown in the summer harvest and four storage conditions to be sown in the second harvest. These are: 1- six months of storage in a cold room at 10º C; 2- three months storage at room temperature and three months in a cold room at 10º C; 3- six months storage at room temperature for planting in the summer crop. For planting in the second harvest: 1- nine months of storage in a cold room at 10º C; 2- three months storage at room temperature and six months in a cold room at 10º C; 3- six months storage at room temperature and three months in a cold room at 10º C; 4- nine months storage at room temperature. It was concluded that the physiological quality of the hybrids seeds 2B647 PW, BM915 PRO and SHS4070 is maintained until the 90 days of storage, independent of the chemical treatment used and the seeds size. The chemical treatment effect on the physiological quality of the seeds is influenced by the genotype. The insecticide addition to the standard treatment used in the seeds chemical treatment does not affect the fungicides action on the fungi present in them. The chemical treatments used and the storage conditions do not interfere in the productivity of hybrids 2B647 PW, BM915 PRO and SHS4070, independently of seed size and sowing time.